MEGI'S BOOK AS AN ATTEMPT TO INCREASE KNOWLEDGE AND REDUCE PLAQUE SCORE FOR CHILDREN WITH INTELLECTUAL DISABILITIES - Malinda Sri Rahayu; Anang Anang; Cahyo Nugroho; Rieza Zulfahmi Taftazani (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background: Intellectual disabilities is a term used to refer to children who experience limitations in their intellectual functioning. Such limitations in the learning process can affect their dental and oral hygiene. A total of 22 children with intellectual disabilities at Cineam State Special Elementary School (SDLB), Tasikmalaya Regency, underwent OHI-S (Simplified oral hygiene index) assessment based on specific criteria. Objective: This study aims to identify the impact of the using of scheduled diary media containing pictures of brushing teeth (MEGI) on the level of knowledge and dental and oral hygiene in children with intellectual disabilities. The research method used is quasi-experimental research with a one group pre-post test design. 33 samples of children with intellectual disabilities were selected using the purposive sampling method. After that, an oral hygiene index (OHI-S) was checked and a questionnaire was distributed to measure their level of knowledge. The collected data was analyzed using the Wilcoxon test with the help of the SPSS application. Results: The results of statistical analysis (p < 0.005), showed  a significant influence between counseling and the level of knowledge and dental and oral hygiene of respondents. Conclusion: The media of megi book”s ith pictures of brushing teeth have a positive influence on increasing knowledge and dental and oral hygiene in children with intellectual disabilities.